EJTIR Discussion notes & replies - Wee, Bert van (European Journal of Transport and Infrastructure Research, 2007)
Starting with this issue, EJTIR plans to complement its regular content with so-called discussion notes & replies. A discussion note can be sent to us by either scholars or practitioners. The approximately sixpage document comments on particular trends, issues or visions in the field of transportation. Such a discussion note, rather than being sent out for review, is forwarded to a number of experts on the topic discussed, with the request to react by means of a brief reply. After having received all replies, the author of the initial discussion note is provided with the opportunity to respond. Subsequently, all documents are published in an EJTIR-issue under the heading discussion notes & replies. We trust that, by extending our content towards including these discussions, we are able to further increase our relevance for scholars and practitioners in the field of transportation: in our view, many of the important transportation challenges ahead of us could benefit from a discussion among experts as sketched above.